Indah Putri Indriani's Strategy in Building a Personal Brand - Zulfiqar; Muhammad; Ariana (Global Writing Academica Researching & Publishing, 2024)
This study aims to explain and analyze the Personal Branding of Indah Putri Indriani in several periods of her leadership in North Luwu. In addition, this study also analyzes the influence of Indah Putri Indriani's personal branding on the people of North Luwu. This study uses a qualitative descriptive research method which is a type of research that is directed at naturalistic research, namely descriptive research that reveals reality naturally as it is. Even so, it still gives the meaning behind the natural events shown by the subject. This type of research is included in the descriptive survey category, namely a community survey. The data used are primary and secondary data. The theory used is Political Marketing Theory and Personal-Branding Theory. The results of the study show that Indah Putri Indriani's personal branding strategy provides an illustration of the strength identity of Indah Putri Indriani. Her participation in the candidacy for Regent of North Luwu for the 2016-2021 period was accompanied by sufficient social and political capital, the female figure and Indah's personality are known to have intelligence and the ability to cultivate the public to be closer to her. Before participating in the regional head election in North Luwu in 2015, Indah Putri Indriani, who was deputy regent for the 2010-2015 period, had studied a lot about the needs and desires of the people that had not been met by the previous North Luwu Regency government. As someone who is engaged in politics, it is the time for young people to contribute to economic growth. Indah Putri Indriani had initiate the MSME Program for young people in North Luwu Regency.